Patients' attitudes to risk in lung cancer surgery: a qualitative study - Powell, Helen A.; Jones, Laura L.; Baldwin, David R.; Duffy, John P.; Hubbard, Richard B.; Tod, Angela M.; Solomon, Josie; Bains, Manpreet (Elsevier, 2015)
Objectives Lung cancer surgery leads to long term survival for some patients but little is known about how patients decide whether to accept the associated surgical risks. The objective of this qualitative study was to explore patients’ attitudes to the risks associated with lung cancer surgery.